Editor's Choice – Outcomes of Self Expanding PTFE Covered Stent Versus Bare Metal Stent for Chronic Iliac Artery Occlusion in Matched Cohorts Using Propensity Score Modelling. (August 2017) - Piazza, M.; Squizzato, F.; Dall'Antonia, A.; Lepidi, S.; Menegolo, M.; Grego, F.; Antonello, M.
Abstract : Objectives: The aim was to compare outcomes of self expanding PTFE covered stents (CSs) with bare metal stents (BMSs) in the treatment of iliac artery occlusions (IAOs). Methods: Between January 2009 and December 2015, 128 iliac arteries were stented for IAO. A CS was implanted in 78 iliac arteries (61%) and a BMS in 50 (49%). After propensity score matching, 94 limbs were selected and underwent stenting (47 for each group). Thirty day outcomes and midterm patency were compared; follow-up results were analysed with Kaplan–Meier curves. Results: Overall, iliac lesions were classified by limb as TASC B (19%), C (21%), and D (60%). Technical success was 98%. Comparing CS versus BMS, the early cumulative surgical complication rate (12% vs. 12%, p  = 1.0) and 30 day mortality rate (2% vs. 2%, p  = 1.0) were equivalent. At 36 months (average 23 ± 17), overall primary patency was similar between CS and BMS (87% vs. 66%, p  = .06), and this finding was maintained after stratification by TASC B ( p  = .29) and C ( p  = .27), but for TASC D, CSs demonstrated a higher patency rate (CS, 88% vs. BMS, 54%; p  = .03). In particular, patency was in favour of CSs for IAOs > 3.5 cm in length ( p  = .04), total lesion length > 6 cm ( p  = .04), and IAO with calcification > 75% of the arterial wall circumference ( p  = .01). Conclusions: Overall, the use of self expanding CS for IAOs has similar early and midterm outcomes compared with BMS. Even if further confirmatory studies are needed, CSs seem to have higher midterm patency rates than BMSs for TASC D lesions, IAOs with a total lesion length > 6 cm, occlusion length > 3.5 cm, and calcification involving > 75% of the arterial wall circumference. These specific anatomical parameters may be useful to the operator when deciding between CS and BMS during endovascular planning.